High-reliability low-temperature Sn-Bi-based lead-free solder alloy
By using the subeutectic double cluster model of β-Sn(Bi) solid solution phase in low-temperature Sn-Bi-based lead-free solder alloy, and adding In, Ag, and Cu elements to optimize the alloy composition, the shortcomings of the solder alloy in terms of toughness, ductility and melting point are solved, and high reliability and suitable effects for low-temperature welding processes are achieved.
Patent Information
- Application Number
- CN202510182017.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-19
AI Technical Summary
The existing low-temperature Sn-Bi-based lead-free solder alloys have shortcomings in toughness and ductility, and have a high melting point, making it difficult to meet the needs of low-temperature welding processes.
The subeutectic double cluster model based on the β-Sn(Bi) solid solution phase was used to add In, Ag, and Cu elements to optimize the alloy composition, including 38.2% Bi, 3.7~4.0% In, 0~1.0% Ag, 0~0.8% Cu, and the balance is Sn to form a high-reliability lead-free solder alloy.
It significantly reduces the melting point of the solder alloy, improves its plasticity and ductility, enhances the strength and drop performance of the solder joints, and is suitable for low-temperature welding processes.
Smart Images

Figure CN119857962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-free solder, and in particular to a low-temperature Sn-Bi based lead-free solder alloy. Background Art
[0002] As consumer electronic products develop towards low power consumption, multifunctionality, high integration, miniaturization, and green manufacturing, new requirements are put forward for electronic manufacturing packaging technology and processes to solve the severe challenges faced by the reliability of consumer electronic products. Up to now, the most mature and widely used lead-free solder system is SAC305 (Sn-3.0Ag-0.5Cu). This lead-free solder has the advantages of good wettability, less solder slag, and high solder joint strength. However, the problem with this solder is that its melting point is as high as 217 o C, which is 34% higher than that of Sn-Pb eutectic solder o C. In addition, the reflow peak temperature of SAC305 needs to reach 250 o C is even higher, which challenges the process and materials used to match Sn-Pb eutectic solder. Not only must the impact of high temperature on device performance be considered, but also the problem of residual thermal stress causing the warping of the printed circuit board (PCB). As electronic packaging develops towards miniaturization and high integration, the thermal management problem caused by high reflow temperature will be magnified geometrically and become more severe. Therefore, the development of low-temperature solder and low-temperature process is also a development direction of the current electronic packaging industry after lead-free.
[0003] In addition, most solar cells in the photovoltaic industry use copper ribbons coated with solder and other types of connector components connected using solder paste. In order to continuously reduce the cost of solar energy, the thickness of cells is getting thinner and thinner. In the next few years, the industry will need to switch from tin-lead solder to lead-free solder. Since the CTE of copper ribbons and other components used to connect cells together can be 4-5 times larger than Si, stress is applied to the fragile cells when the solder solidifies after the processing process. As the cell becomes thinner, it also becomes more and more prone to breakage. Using low melting point solder alloys and solder pastes can reduce the occurrence of these problems and reduce the risk of cell breakage.
[0004] In electronic packaging, solder alloys with melting points lower than SAC305 are generally called low-temperature solders. Sn-Bi solders have the advantages of low melting point, low cost, good wettability and high strength, and have greater room for development compared to other low-temperature lead-free solder systems. However, Sn-Bi eutectic solders also have the problems of large Bi phase brittleness and poor ductility. During the aging process, Cu 3Problems such as Bi segregation are prone to occur at the Sn / Cu interface, among which poor ductility and low plasticity are the most important problems of Sn-Bi solder. At present, the solution to this problem mainly includes two directions: 1) reducing the Bi content to reduce the segregation of the brittle Bi phase; 2) adding alloy elements that are beneficial to improving toughness, such as In, Ag, etc.
[0005] Existing public documents disclose that for Sn-Bi based solder alloys, reducing the Bi content within a certain range can effectively improve toughness. The Chinese patent application with the publication number CN115383349A discloses a method for obtaining a high-toughness lead-free tin-bismuth solder by microalloying and regulating the microstructure, wherein the weight percentage of the main component Bi is 40%, and its elongation is increased by 26.6% compared with Sn-58Bi, and the IMC growth is avoided during the aging process. Existing public documents also disclose that adding a small amount of alloying elements to Sn-Bi can improve the impact resistance of the solder joint. The Chinese patent application with the publication number CN111683785A discloses a solder alloy, wherein the weight percentage of the main component Bi is 35 ~ 68%, the weight percentage of In is 0.5 ~ 3%, and other trace elements such as Pd, Co, Ge are included. This kind of lead-free solder can effectively refine the brittle Bi phase and show excellent impact resistance, but the problem it has is that the toughness of the alloy is still difficult to meet the needs in practical applications. Adding In element can improve the toughness of alloy to a certain extent, but its content is low and difficult to significantly improve the performance of alloy. In addition, the trace alloy species added in this solder are too many, which is unfavorable for the uniformity of organization and the stability of performance. The Chinese patent application with publication number CN117900692A discloses a Sn-Bi-In-Ag lead-free solder based on traditional {cluster} (connected atoms) model, wherein the weight percentage of main component Sn is 45.5 ~ 46.5% or 51.5 ~ 52.0%, and the weight percentage of In is 2.9 ~ 3.1% or 3.35 ~ 3.4%. This lead-free solder alloy can slightly improve shear strength, but due to the double cluster model used, the composition deviation caused by the influence of solid solution phase is not taken into account, and its shear strength is only 28.6 MPa. Summary of the invention
[0006] The purpose of the present invention is to improve the performance of existing low-temperature Sn-Bi based lead-free solder, further improve the plasticity and ductility of the low-temperature Sn-Bi based lead-free solder, and reduce the melting point, so as to better apply it to the high-reliability low-temperature Sn-Bi based lead-free solder alloy in the low-temperature welding process.
[0007] The technical solution adopted by the present invention is as follows: A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, In, Ag, and Cu atoms are added to replace Sn atoms to obtain a high-reliability lead-free solder alloy, the alloy composition, by mass percentage, includes 38.2% Bi, 3.7-4.0% In, 0-1.0% Ag, 0-0.8% Cu, and the remainder is Sn; the hypoeutectic dual-cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 The analytical expression of the hypoeutectic double cluster is: 8[Sn-Sn 10 ] 3 In 1 + 2[Sn-Sn 10 ] 3 Sn 1 + 1[Bi-Bi 6 ] 5 = Sn 112 Bi 42 In 8 = Sn-38.2Bi-3.9In.
[0008] Preferably, in the alloy, the mass content of In is 3.9%, and the mass content of Ag is 0.94%; the hypoeutectic double cluster model of the alloy, 8[Sn-Sn 10 ] 3 In 1 + 2[Sn-Sn 10 ] 3 Ag 1 + 1[Bi-Bi 6 ] 5 =Sn 110 Bi 42 In 8 Ag 2 = Sn-38.2Bi-3.9In-0.94Ag.
[0009] In the traditional {cluster} (connected atoms) model, Sn 57 Bi 43 The dual cluster model of the eutectic alloy consists only of the structural units representing Sn [Sn-Sn 10 ] Sn 5 and the structural unit representing Bi [Bi-Bi 6 ] 5The cluster is simply mixed in a ratio of 1:1, and the cluster formula is: 1[Sn-Sn 10 ] Sn 5 + 1[Bi-Bi 6 ] 5 = Sn 16 Bi 12 = Sn 57.1 Bi 42.9 This model does not take into account the influence of the β-Sn(Bi) solid solution phase. However, the low-temperature Sn-Bi based lead-free solder of the present invention, in its dual cluster model, contains the structural unit of the β-Sn(Bi) solid solution phase as [Sn-Sn 10 ] 3 Sn 1 , after optimization, Sn 57 Bi 43 The analytical formula of the double cluster of eutectic alloy is: 2[Sn-Sn 10 ] 3 Sn 1 + 1[Bi-Bi 6 ] 5 = Sn 24 Bi 18 = Sn 57.1 Bi 42.9 .
[0010] Based on the double cluster model including the solid solution phase, the present invention further analyzes the Sn-Bi binary hypoeutectic double cluster analytical formula and the multi-cluster analytical formula of the Sn-Bi-In-X alloy composition. 10 ] 3 Sn 1 + 1[Bi-Bi 6 ] 5 = Sn 120 Bi 42 = Sn-38.2Bi and 8[Sn-Sn 10 ] 3 In 1 + 2[Sn-Sn 10 ] 3 Ag 1 + 1[Bi-Bi 6 ] 5 = Sn 110 Bi 42 In 8 Ag 2 = Sn-38.2Bi-3.9In-0.94Ag. The present invention designs the multi-element alloy composition more accurately, thereby obtaining an alloy with good comprehensive properties.
[0011] The solder alloy of the present invention reduces the Bi content on the basis of the Sn-58Bi eutectic alloy. Under the condition of ensuring a low reflow process temperature, the Bi content is reduced to the composition range of the hypoeutectic Sn-Bi, thereby reducing the risk of Bi atoms being segregated at the interface due to the brittle Bi phase during the reflow process, and reducing the Bi in the Cu during the aging process. 3 The tendency of Sn / Cu segregation is increased, and the hypoeutectic Sn-Bi component is transformed from the Sn-Bi eutectic structure to the mixed structure of Sn-Bi eutectic and β-Sn, and the toughness of the β-Sn phase is improved compared with the eutectic structure. A certain amount of In element is added on the basis of reducing the Bi content. The crystal structures of In and Sn are both tetragonal structures, so In is more likely to replace Bi as a solute atom in β-Sn, which can reduce the lattice distortion of β-Sn and thus improve the toughness. In addition, the addition of In can also reduce the liquidus temperature of the solder. In as the main added element doped into the Sn-Bi hypoeutectic solder is not only expected to improve the toughness of the solder, but also to further reduce the process temperature of the solder, thereby improving the low-temperature solderability of the solder. The amount of In added has a great influence on the performance of the Sn-Bi based solder. When the In content is less than 2 wt.%, the toughness of the solder alloy is difficult to be significantly improved. When the In content is higher than 5 wt.%, the precipitation of BiIn phase will be observed in the microstructure. The formation of this compound will lead to a sharp deterioration of performance and increased brittleness. In addition, the maximum solid solubility of In in Sn is about 7 wt.%. In the designed Sn-Bi based solder, when the Bi content is 35 ~ 45 wt.%, the corresponding maximum solid solubility of In should be in the range of 3.85 ~ 4.55 wt.%, so as to avoid the formation of InSn 4 In summary, by adjusting the In / Sn ratio so that the In content is 3.7 ~ 4.0 wt.%, the performance of the Sn-Bi based alloy can be most effectively optimized.
[0012] The effect of trace addition of Cu element is not significant on the melting point of solder. Its main function is to form Cu with high melting point during smelting. 6 Sn 5 IMC acts as a site for heterogeneous nucleation to refine the structure. The presence of this second phase hinders the movement of dislocations and thus helps to improve the strength of the solder joint. However, both strengthening effects depend on the size and specific distribution of the second phase. The effect of trace addition of Ag is similar to that of Cu, but the addition of 0.1 ~ 1.5% Ag is conducive to the formation of granular Ag. 3 Sn has a significant effect on matrix dispersion strengthening, and the addition of Ag can further improve the toughness of the solder.
[0013] The Sn-Bi based lead-free solder of the present invention has the following beneficial effects: 1) The liquidus of the solder alloy included in the present invention is lower than that of the hypoeutectic Sn-Bi solder with the same Bi content, and can be reduced by as much as 10 o C, the solder alloy can match the peak value of 185 o The low-temperature reflow process of about C can be applied to low-temperature welding or mixed assembly fields.
[0014] 2) The solder alloy of the present invention reduces the Bi content to the composition range of hypoeutectic Sn-Bi under the condition of ensuring a low reflow process temperature, inhibits the Bi atoms from segregating at the interface to form a brittle phase during the reflow process, and improves the toughness of the β-Sn matrix. While not reducing the strength of the solder joint, the drop performance of the solder joint is improved.
[0015] 3) Adding In element, In element can be dissolved in β-Sn matrix to strengthen the matrix. By adjusting the mass ratio of In / Sn, the poor plasticity and insufficient toughness of Sn-Bi based solder alloy can be improved; at the same time, the formation of InSn can be avoided. 4 In element reacts with Cu and Sn elements during the interface reaction. The formation of appropriate thickness IMC can improve the shear strength and shear displacement of the solder joint. In addition, the addition of In element can reduce the melting point of solder.
[0016] 4) Adding Ag and (or) Cu alloy elements to the Sn-Bi-In alloy will form corresponding intermetallic compounds, which can refine the structure and solve the problem of microstructure coarsening of the solder alloy caused by the addition of In elements. The addition of Ag and Cu elements improves the wetting performance of the solder joint and improves the problem of deterioration of wetting performance caused by the addition of In elements.
[0017] 5) The elements contained in the solder alloy of the present invention are non-toxic and harmless, and meet the requirements of green environmental protection in the development of the electronics industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a 100× scanning image of the microstructure of Example 1-6; Figure 2 is a 100× scanning image of the microstructure of Comparative Examples 1-9; Figure 3 It is the characterization of the gray phase, phase boundary and white phase region of Comparative Example 1, Example 1 and Example 5; Figure 4 are 300× scanning images of the microstructures of Example 5 and Comparative Example 8; Figure 5 is the shear strength of each solder joint; Figure 6 is the shear displacement of each solder joint; Figure 7 is the wetted area of each solder. DETAILED DESCRIPTION
[0019] In order to explain the content of the present invention more clearly, the present invention will be described in detail below in conjunction with embodiments and drawings. Example 1
[0020] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy is disclosed. The alloy is based on a hypoeutectic dual cluster model containing a β-Sn(Bi) solid solution phase, and In is added to obtain a high-reliability lead-free solder alloy. The alloy composition, by mass percentage, includes 38.2% Bi, 3.9% In, and the remainder is Sn. The purity of Sn, Bi, and In is 99.99%. The hypoeutectic dual cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 The analytical expression of the hypoeutectic double cluster is: 8[Sn-Sn 10 ] 3 In 1 + 2[Sn-Sn 10 ] 3 Sn 1 + 1[Bi-Bi 6 ] 5 = Sn 112 Bi 42 In 8 = Sn-38.2Bi-3.9In.
[0021] The preparation method of the solder alloy is as follows: 1) Prepare the solder alloy according to the mass percentage and place it in a high temperature resistant quartz tube; 2) Use a hydrogen flame to melt and seal one end of the quartz tube, melt the other end into a narrow opening, and use a vacuum pump to evacuate the air in the tube. Then melt and seal the narrow opening. 3) Place the quartz tube in a high frequency melting furnace and heat to 700 o C and melted at 700 o C is kept warm for at least 5 hours. During the melting period, the quartz tube is shaken every half an hour to ensure that the liquid solder alloy in the quartz tube is more uniform. 4) After the smelting is completed, the furnace is cooled to 300 o C. Then take out the quartz tube and put it into cold water for quenching to ensure that the brazing alloy equilibrium structure can be completely cooled and solidified at high temperature; 5) After the temperature of the quartz tube drops to room temperature, break the quartz tube and take out the brazing alloy ingot. Example 2
[0022] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, In and Cu are added to obtain a high-reliability lead-free solder alloy, the alloy composition, by mass percentage, includes 38.2% Bi, 4.0% In, 0.28% Cu, and the remainder is Sn. The purity of Sn, Bi, In, and Cu is 99.99%. The hypoeutectic dual-cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 The analytical expression of the hypoeutectic double cluster is: 8[Sn-Sn 10 ] 3 In 1 + 1[Sn-Sn 10 ] 3 Sn + 1[Sn-Sn 10 ] 3 Cu 1 + 1[Bi-Bi 6 ] 5 =Sn 111 Bi 42 In 8 Cu 1 = Sn-38.2Bi-4.0In-0.28Cu.
[0023] The preparation method of the solder alloy is the same as that of Example 1. Example 3
[0024] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, the alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, In and Ag are added to obtain a high-reliability lead-free solder alloy, the alloy composition, by mass percentage, includes 38.2% Bi, 3.9% In, 0.47% Ag, and the remainder is Sn. The purity of Sn, Bi, In, and Ag is 99.99%. The hypoeutectic dual-cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 The analytical expression of the hypoeutectic double cluster is: 8[Sn-Sn 10 ] 3 In 1 + 1[Sn-Sn10 ] 3 Sn 1 + 1[Sn-Sn 10 ] 3 Ag 1 + 1[Bi-Bi 6 ] 5 =Sn 111 Bi 42 In 8 Ag 1 = Sn-38.2Bi-3.9In-0.47Ag.
[0025] The preparation method of the solder alloy is the same as that of Example 1. Example 4
[0026] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy, based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, is obtained by adding In and Cu, and the alloy composition, by mass percentage, includes 38.2% Bi, 3.76% In, 0.70% Cu, and the remainder is Sn. The purity of Sn, Bi, In, and Cu is 99.99%. The hypoeutectic dual-cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 , the analytical expression of the hypoeutectic double cluster is: 15[Sn-Sn 10 ] 3 In 1 + 5[Sn-Sn 10 ] 3 Cu 1 + 2[Bi-Bi 6 ] 5 =Sn 220 Bi 84 In 15 Cu 5 = Sn-38.2Bi-3.76In-0.7Cu.
[0027] The preparation method of the solder alloy is the same as that of Example 1. Example 5
[0028] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy, the alloy is based on a hypoeutectic dual cluster model containing a β-Sn(Bi) solid solution phase, In and Ag are added to obtain a high-reliability lead-free solder alloy, the alloy composition, by mass percentage, includes 38.2% Bi, 3.9% In, 0.94% Ag, and the remainder is Sn. The purity of Sn, Bi, In, and Ag is 99.99%. The hypoeutectic dual cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] 3 Sn 1 The analytical expression of the hypoeutectic double cluster is: 8[Sn-Sn 10 ] 3 In 1 + 2[Sn-Sn 10 ] 3 Ag 1 + 1[Bi-Bi 6 ] 5 =Sn 110 Bi 42 Ag 2 In 8 = Sn-38.2Bi-3.9In-0.94Ag.
[0029] The preparation method of the solder alloy is the same as that of Example 1. Example 6
[0030] A high-reliability, low-temperature Sn-Bi-based lead-free solder alloy. The alloy is based on a hypoeutectic dual-cluster model containing a β-Sn(Bi) solid solution phase, and In, Ag, and Cu are added to obtain a high-reliability lead-free solder alloy. The alloy composition, by mass percentage, includes 38.2% Bi, 3.76% In, 0.42% Cu, 0.47% Ag, and the remainder is Sn. The purity of Sn, Bi, In, Cu, and Ag is 99.99%. The hypoeutectic dual-cluster model of the alloy contains a structural unit of [Sn-Sn 10 ] 3 Sn 1 , the analytical expression of the hypoeutectic double cluster is: 15[Sn-Sn 10 ] 3 In 1 + 3[Sn-Sn 10 ] 3 Cu 1 + 2[Sn-Sn 10 ] 3 Ag 1 +2[Bi-Bi6 ] 5 = Sn 220 Bi 84 In 15 Cu 5 Ag 2 = Sn-38.2Bi-3.76In-0.47Ag-0.42Cu.
[0031] Comparative Example 1
[0032] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 38.2%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0033] Comparative Example 2
[0034] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0035] Comparative Example 3
[0036] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 58%, and the balance is Sn. The solder alloy preparation method is the same as that of Example 1.
[0037] Comparative Example 4
[0038] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0039] Comparative Example 5
[0040] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, Cu: 0.26%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0041] Comparative Example 6
[0042] A low-temperature Sn-Bi-based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, Ag: 0.45%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0043] Comparative Example 7
[0044] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, Cu: 0.68%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0045] Comparative Example 8
[0046] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, Ag: 0.92%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0047] Comparative Example 9
[0048] A low-temperature Sn-Bi based lead-free solder alloy, wherein the components by mass percentage are: Bi: 42.3%, In: 3.5%, Cu: 0.40%, Ag: 0.45%, and the balance is Sn. The preparation method of the solder alloy is the same as that of Example 1.
[0049] The solders of the above embodiments and comparative examples were subjected to DSC test to obtain their melting points and determine the corresponding brazing process of the solders. The test temperature range was 50 o C~250 o C, heating and cooling rate is 10 o C / min. The melting points of the solder alloys were measured and are shown in Table 1.
[0050] Table 1. Melting points of solder alloys
[0051] The microstructure images of Examples 1 to 5 are shown in Figure 1 The microstructure images of Comparative Examples 1 to 9 are shown in Figure 2 .
[0052] Comparative Example 1 does not add In element, while Example 1 adds In element, In is mainly dissolved in the β-Sn phase, playing a role of solid solution strengthening. Example 2 to Example 6 add a certain amount of Cu and / or Ag elements on the basis of the corresponding components of Example 1, and it can be observed that the microstructure is significantly refined.
[0053] The areas of the gray phase, phase boundary and white phase of Comparative Example 1, Example 1 and Example 5 were statistically analyzed. Figure 3 As shown. Due to the addition of In element, the gray-white phase interface area of Example 1 is significantly increased. After adding In and Ag elements at the same time, the white phase area of Example 5 is larger, and the Bi phase is more dispersed and uniform.
[0054] In Example 2, Example 4, Example 6, Comparative Example 5, Comparative Example 7, and Comparative Example 9, the solder alloy composition contains Cu element, and dark Cu can be observed. 6 (Sn,In) 5 Phase separation.
[0055] The solder alloy composition of Example 3, Example 5, Example 6, Comparative Example 6, Comparative Example 8, and Comparative Example 9 contains Ag element, and gray Ag can be observed. 3 Precipitation of (Sn,In) phase.
[0056] The microstructure images of Example 5 and Comparative Example 8 at 300× are as follows: Figure 4 It can be observed that the precipitated phase Ag in Example 5 (Sn-38.2Bi-3.9In-0.94Ag) 3 The size of (Sn, In) is significantly smaller than that of the precipitated phase in Comparative Example 8 (Sn-42.3Bi-3.5In-0.92Ag). Large-sized precipitated phases are not conducive to improving the mechanical properties of solder joints.
[0057] The shear strength test was carried out on the example and comparative alloys. The solder joints prepared from the example and comparative alloys were loaded on a tensile machine and the shear test was carried out at a rate of 0.3 mm / min. The shear strength results and shear displacement data are shown in Tables 1 and 2. Figure 5 and Figure 6 .
[0058] Example 5 (Sn-38.2Bi-3.9In-0.94Ag) has both the best shear strength and shear displacement.
[0059] Wetting test was performed on the alloys of the embodiment and comparative example. The specific operation was as follows: 1) Prepare 3 solder balls of 10 mg and place them on a copper sheet with a polished surface. 2) Perform reflow treatment according to the set reflow curve, and clean the residual flux with ethanol after reflow. 3) Measure the wetting area. Photoshop was used to measure the wetting area. The average value of three groups of each component was taken. The area data after wetting is shown in Figure 3. Figure 7 .
[0060] Compared with Sn-Bi alloy, after adding In element, the plasticity of Sn-Bi-In alloy is improved, but the wettability is reduced. On the basis of Sn-Bi-In alloy, after adding Ag element, the plasticity of Sn-Bi-In-Ag alloy is further improved, and the wettability is also improved at the same time.
[0061] It can be seen from the examples and comparative examples that the melting point of the low-temperature Sn-Bi-based lead-free solder of the present invention is significantly reduced, all to below 128.7°C. Each example (Sn-38.2Bi-X) corresponds to the comparative example (Sn-42.3Bi-X) with the same elements added, except that only the Bi content is significantly reduced, and In, Ag, and Cu are slightly changed. While ensuring a significant increase in strength, plasticity and ductility are significantly improved. It can be better applied to low-temperature welding processes.
[0062] The low-temperature solder of the present invention has the advantages of low melting point, high plasticity and toughness, high shear strength, and can match the current industrial medium and low temperature reflow process. It is suitable as a new low-temperature solder for use in low-temperature brazing application scenarios such as consumer electronic products or new solar cells.
[0063] Unless otherwise specified, all percentages described in the present invention are by mass percentages.
Claims
1. A high reliability, low temperature Sn-Bi based lead-free solder alloy, characterized in that: The alloy is based on a hypoeutectic double cluster model containing a β-Sn(Bi) solid solution phase, and In, Ag, and Cu atoms are added to replace Sn atoms to obtain a high-reliability low-temperature lead-free solder alloy. The alloy composition, by mass percentage, includes 38.2% Bi, 3.7-4.0% In, 0-1.0% Ag, 0-0.8% Cu, and the remainder is Sn; the hypoeutectic double cluster model of the alloy, the structural unit containing the β-Sn(Bi) solid solution phase is [Sn-Sn 10 ] Bi3Sn1, the hypoeutectic double cluster analytical expression is: 8[Sn-Sn 10 ] Bi3In1 + 2[Sn-Sn 10 ]Bi3Sn1 + 1[Bi-Bi6]Bi5 = Sn 112 Bi 42 In8 = Sn-38.2Bi-3.9In.
2. A high reliability low temperature Sn-Bi based lead-free solder alloy according to claim 1, characterized in that: The alloy has a composition of 38.2% Bi, 3.9% In, 0.94% Ag, and the remainder Sn in terms of mass percentage. The hypoeutectic double cluster model of the alloy is 8[Sn-Sn 10 ] Bi3In1 + 2[Sn-Sn 10 ] Bi3Ag1 + 1[Bi-Bi6] Bi5 = Sn 110 Bi 42 In8Ag2 = Sn-38.2Bi-3.9In-0.94Ag.
Citation Information
Patent Citations
SnBiSb-series low-temperature lead-free solder and preparation method thereof
CN106216872A
Method for obtaining high-toughness lead-tin-bismuth-free solder through microalloying regulation and control of microstructure
CN115383349A
Sn-Bi-In-Ag lead-free solder suitable for low-temperature welding and preparation method of Sn-Bi-In-Ag lead-free solder
CN117900692A
Composite lead-free solder for brazing
CN119387946A
Lead-free solder alloy, method for manufacturing the same, mounting structural body, mounting method, lead-free fuse alloy, method for manufacturing the same, plate fuse, lead-free alloy, and method for manufacturing the same
JP2005238328A